2009
DOI: 10.1063/1.3194287
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-state selection, alignment, and orientation of large molecules using static electric and laser fields

Abstract: Supersonic beams of polar molecules are deflected using inhomogeneous electric fields. The quantumstate-selectivity of the deflection is used to spatially separate molecules according to their quantum state. A detailed analysis of the deflection and the obtained quantum-state selection is presented. The rotational temperatures of the molecular beams are determined from the spatial beam profiles and are all approximately 1 K. Unprecedented degrees of laser-induced alignment ( cos 2 θ2D = 0.972) and orientation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
238
2
9

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 149 publications
(259 citation statements)
references
References 73 publications
(99 reference statements)
10
238
2
9
Order By: Relevance
“…Finally, the TOF spectra, which indicate the degree of orientation, show a backward-forward asymmetry of 58/42 ( Figure 6 e) for the undeflected molecules, which increases to 67/33 ( Figure 6 f) for the deflected molecules. In summary, even when the intensity of the YAG alignment pulse is lowered by an order of magnitude a strong degree of 3D alignment and orientation is maintained, in accordance with previous findings for 1D alignment and orientation [21,23].…”
Section: Alignment and Orientation At Low Laser Intensitysupporting
confidence: 92%
See 1 more Smart Citation
“…Finally, the TOF spectra, which indicate the degree of orientation, show a backward-forward asymmetry of 58/42 ( Figure 6 e) for the undeflected molecules, which increases to 67/33 ( Figure 6 f) for the deflected molecules. In summary, even when the intensity of the YAG alignment pulse is lowered by an order of magnitude a strong degree of 3D alignment and orientation is maintained, in accordance with previous findings for 1D alignment and orientation [21,23].…”
Section: Alignment and Orientation At Low Laser Intensitysupporting
confidence: 92%
“…Optimizing the degree of orientation in the mixed laser and static electric field method imposes, however, an even stronger requirement on the initial rotational state distribution. Recently, we showed that 1D orientation, using the mixed-field method, can be strongly enhanced by using rotational-quantum-state selected molecules as targets [21,23]. The state selection is obtained by passing arXiv:0906.2971v2 [physics.chem-ph] 4 Aug 2009 a cold molecular beam through an electrostatic deflector that spatially disperses molecules according to their rotational quantum state.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, we can sort the resulting states of each H M i by energy and assign quantum number labels in the same order as for energy-sorted field-free states of the same symmetry. This yields a correct assignment of ''adiabatic quantum number labels'',JK aKcM , to rotational states in the field [20]. (For interpretation of the references to colour in this figure legend, the reader is referred to the web version of this article.…”
Section: Asymmetric Topmentioning
confidence: 97%
“…The corresponding Hamiltonian matrix and the strategy of its diagonalization are described in following sections for each type of rotor. Finally, the program assigns the calculated rotational energies in the field to ''adiabatic quantum numbers'', i. e., to the adiabatically corresponding field-free rotor states [20]. To ensure correct assignments, a symmetry classification of H rot, ε and quantum states according the electric field symmetry group [21,22] is required.…”
Section: Overviewmentioning
confidence: 99%
“…In the current experiment (see supporting information for details) a supersonic molecular beam is used to produce a cold water sample in the gas-phase with a rotational temperature of 8 K, corresponding to > 99 % of para and > 96 % of ortho molecules in their absolute ground state, respectively. The molecular beam is then dispersed perpendicular to its flight direction according to the effective-dipole-moment- to-mass ratio (µ eff /m) using strong inhomogeneous electric fields [27,30] . Water molecules are quantum state selectively ionized via (2+1) resonance-enhanced multiphoton ionization (REMPI); a spectrum is shown in the supporting information.…”
mentioning
confidence: 99%